Perbandingan kekuatan kompresi struktur laminasi dan prepreg dari komposit jute-epoxy - Adi Yoga Saputra, Gede; Astika, I Made; Ary Subagia, I.D.G (Jurnal Energi Dan Manufaktur; Vol 14 No 1 (2021)DO - 10.24843/JEM.2021.v14.i01.p05, 2022)
This experiment has conducted to investigate mechanical properties of pipe structure performed by natural composite. The composite has been fabricated in two modes such laminate and prepreg reinforcement by vacuum injection molding. Compression test have been conducted for each variety in five times repeating. The specimen was made and test according to the ASTM D2166M-16 standard. The purpose of this research is to investigate and comparation of compression strength of laminate and prepreg structure composite pipe. The test result shows that laminates mode of pipe composite using the woven jute fabric has a lower in compression strength about 711.34 [MPa] compared to prepreg mode about 1184.9 [MPa]. In addition, the young modulus of the laminate composites has about 5.37 [GPa], and the prepreg mode has value about 6. 885 [GPa]. This value indicates that the prepreg mode more strength than the laminates mode in composite pipe due to the prepreg in tangential direction the compression energy absorbed by the fiber absolutely.